IDENTIFICATION AND CHARACTERIZATION OF DIFFERENT POTENTIALLY ANTIBACTERIAL COMPOUNDS FROM A MARINE STREPTOMYCES SP. SP1 - B. M. Atallah; E. El-Mohsnawy; W. A. El-Shouny; S. A. Haroun (Journal of Animal and Plant Sciences, 2023)
Due to the overuse of antibiotics and the rise in the frequency of multidrug-resistant bacteria (MDR), the development of novel antibiotics is one of the most pressing needs today. In the present study, the marine actinomycete Streptomyces sp. Sp1 was isolated for the first time from Lake Burullus,Nile Delta, Egypt. Streptomyces sp. Sp1 was identified via morphological and biochemical techniques. Furthermore, it was identified on the basis of 16S rRNA gene sequence that was analyzed using the BLAST-N tool (Basic Local Alignment Search Tool-Nucleotides) from the NCBI website (National Center for Biotechnology Information). Streptomyces sp. Sp1 exhibited high antibacterial activity against three serious multidrug resistant pathogens, Listeria monocytogenes, Staphylococcus aureus and Pseudomonas aeruginosa. The potential antibacterial compounds produced by Streptomyces sp. Sp1 were analyzed using gas chromatography-mass spectroscopy (GC-MS). It confirmed the presence of five bioactive compounds; broxyquinoline, 9-aminoacridine, 9,10-anthracenedione, harmine and ricinoleic acid that have different antimicrobial mechanisms.The great antibacterial activity of Streptomyces sp.Sp1 could be explained by combination of the different antimicrobial mechanisms of these compounds.
Keywords: Streptomyces sp.SP1; characterization; antibacterial; identification